Indonesian EAP Students’ Vocabulary Level and Size: An Empirical Investigation - Fenty Lidya Siregar (Lingua Cultura, 2020)
The research aimed to know to what extent Indonesian English for Academic Purposes (EAP) students master high and midfrequency words (4.000-5.000). Besides, it aimed to know the vocabulary size of Indonesian EAP students. To fill the gap, the research examined 128 Indonesian EAP students from two private universities in Indonesia. To gather its data, the research employed the Vocabulary Level Test of Webb, Sasao, & Ballance, and the Vocabulary Size Test of Nation and Beglar. The research findings indicate that the participants have not yet mastered the high-frequency words and the mid frequency words from 4.000-5.000 word-families. The finding also reveals that the mean scores of the students’ vocabulary range between 6.000 and 10.000. It implies that the previous learning of the participants has not yet facilitated them to learn important vocabulary from 1.000 to 5.000 word-families. Thus, although they have a big vocabulary size, they might face problems when trying to understand some texts. The research findings are expected to increase English teachers’ awareness in general and EAP teachers’ awareness specifically of the importance of facilitating their students to learn high-frequency words.